Tensile Properties Study on AZ91D Magnesium Alloy through Gas Nitriding - Azmi, Muhammad Adib Aiman (2018)
This project was conducted to study the tensile property study on the Nitrogen element on a material. The material used as a specimen in describing the tensile properties is magnesium alloy, MgAZ91D. Through this study, magnesium alloy MgAZ91D has went through surface heat treatment with Nitrogen rich environment which can be refer to as Gas Nitriding through different heat treatment parameters in order to obtain the enhanced material properties. Magnesium alloy MgAZ91D specimens went through the nitriding process at temperature of 300 °C, 400 °C, 500 °C with fixed pressure with 1 hours and 2 hours of exposure. A study on the microstructure of the MgAZ91D specimens has been done to correlate with the parameters being used for the nitriding process. The sample of nitrided and non-nitrided samples went through tensile testing to observe the effects of nitriding on mechanical tensile properties of the specimens. During microstructure study, condition on the specimens after being nitride has been identified by using Variable Pressure – Field Emission Scanning Electron Microscope (VP-FESEM) and Energy Dispersive X-ray (EDX). These methods are crucial in order to observe the nitrogen distribution on magnesium alloy MgAZ91D and to correlate it with the tensile properties of the specimens.